APPLICATION OF BRACON ENTOMOPHAGE AGAINST THE SOUTHERN WAREHOUSE MOTH DURING THE STORAGE OF AGRICULTURAL PRODUCTS - Sulaymonov Inoyatullo Novatullo o‘g‘li (Bright Mind Publishing, 2026)
The article describes the morphological, biological characteristics of the Bracon hebetor parasite and the effectiveness of its use in the fight against the southern storage moth (Plodia interpunctella) during the storage of agricultural products.